Antibacterial Effect of Green Synthesis of Selenium Nanoparticles against Salmonella typhi in Small Buffalo - AL-Roomi , Noora Majid; Ajeel , Hameedah Hamza (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Salmonella typhi is one of the most significant public causes of diarrhea in young animals. Bacterial colonies were first diagnosed by bacteriological methods. The aim of this article is to study the antibacterial effect of green synthesis of selenium nanoparticles against salmonella typhi in small buffalo. From 60 fecal samples of diarrhea, Salmonella typhi consisted of 21(35%) Salmonella paratyphi 9(15%), Escherichia coli 10(16,66%), Shigella 8(13,33%) and Staphylococcus aureus 12(20%). Cinnamon extract was utilized for the green synthesis of selenium nanoparticles (SeNPs). The characterization of green SeNPs was detected using: UV–Visible Spectroscopy. The absorption peak appeared at 298 nm. X-ray diffraction (XRD) indicated that the formed Se-NPs were highly crystalline. FTIR analysis indicated the presence of N-C– and –C-C stretching groups, amines, and Carbohydrates in the composition of SeNPs, by SEM the Se-NPs had a virtually spherical form. The size of the Se-NPs was made from cinnamon extract in the ranges of 34.5 to 45 nm. The antibacterial activity of the cinnamic ethanolic extract and synthesized SeNPs each one alone was investigated against salmonella typhi by using the agar well diffusion method and tested by using a concentration of (25,50,100 μg/mL). The results indicate that Se-NPs gave a good inhibition at 100 mg/ml, which was 14.33 mm, while the cinnamon extract at the same concentration gave an inhibition of 12.33 mm. The broth microdilution method was used to determine the MIC and MBC. MIC values recorded 200 and 25 μg/mL for cinnamon extract and SeNPs Respectively. Additionally, MBC values were recorded at 800 and 200 μg/mL for cinnamon extract and for SeNPs respectively. The RT-PCR was used for the detection of Bss and Bssr gene expression before and after being treated with green synthesized Se-NPs.The results show that the expression of the BssS and BssR gene after treatment with a combination of SeNPs and cinnamon extract increased in the cycle number and gave high gene expression.